2002
DOI: 10.1001/archpedi.156.6.545
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms for Interleukin 1β Exon 5 and Interleukin 1 Receptor Antagonist in Taiwanese Children With Febrile Convulsions

Abstract: The IL-1Ra allele I is associated with a higher susceptibility to febrile convulsion, which may become a useful marker for predicting the development of febrile convulsions. The IL-1 beta exon 5 gene polymorphisms are not a useful marker for predicting the susceptibility to febrile convulsions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 46 publications
3
44
0
Order By: Relevance
“…In our previous studies, we found an association between a common polymorphism of the gene encoding the IL-1 receptor antagonist and FSs in children (13). In contrast, we noted that KCNQ2 polymorphism was not a useful marker to predict FSs (14).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In our previous studies, we found an association between a common polymorphism of the gene encoding the IL-1 receptor antagonist and FSs in children (13). In contrast, we noted that KCNQ2 polymorphism was not a useful marker to predict FSs (14).…”
Section: Discussionmentioning
confidence: 63%
“…We previously used single-nucleotide polymorphisms as a tool to search for genetic makers of FSs (13,14). Single-nucleotide polymorphisms are the most abundant types of DNA sequence variation in the human genome (15,16).…”
mentioning
confidence: 99%
“…IL1B À511 C to T has been associated with gastric cancer, 21 Parkinson's disease, 22 asthma, 23 increased risk of febrile seizures 24 and inflammatory bowel disease, 25 while IL1B þ 3953 C to T has been associated with periodontitis 26 and inflammatory bowel disease. 25 An 86 bp repeat in the IL1RN gene has also been associated with a number of clinical conditions, including ankylosing spondylitis, 27 susceptibility to sepsis, 28,29 increased risk of death due to sepsis, 30 increased risk of febrile seizures 31 and susceptibility to tuberculosis. 32 One of the major factors contributing to mortality due to malaria infection is cerebral complications.…”
Section: Introductionmentioning
confidence: 99%
“…In a population of individuals of European ancestry, the data revealed no association between IL-1β gene variation and TLE + hippocampal sclerosis (HS) [17] . The other gene polymorphism, IL-1β exon 5, is not significantly associated with susceptibility to FSs [20,21] (for a summary, see Table 2). …”
mentioning
confidence: 99%
“…The IL-1Ra gene, IL-1Ra allele I, is associated with a higher susceptibility to FSs [20,21] . IL-1Ra intron 2 variable tandem repeat polymorphisms are significantly associated with resistance to FSs [23] .…”
mentioning
confidence: 99%